Chronic administration of atypical antipsychotics improves behavioral and synaptic defects of STOP null mice - Delotterie, David (Springer-Verlag, 2010)
Recent studies have suggested that schizophrenia is associated with alterations in the synaptic connectivity involving cytoskeletal proteins. The microtubule-associated protein STOP (Stable Tubule Only Polypeptide) plays a key-role in neuronal architecture and synaptic plasticity and it has been demonstrated that STOP gene deletion in mice leads to a phenotype mimicking aspects of positive and negative symptoms and cognitive deficits classically observed in schizophrenic patients. In STOP-null mice, behavioral defects are associated with synaptic plasticity abnormalities including defects in long-term potentiation. In these mice, long-term administration of typical antipsychotics has been shown to partially alleviate behavioral defects but, as in humans, such a treatment was poorly active on deficits related to negative symptoms and cognitive impairments. Here, we assessed the effects of risperidone and clozapine, two atypical antipsychotics, on STOP-null mice behavior and synaptic plasticity. Long-term administration of either drug results in alleviation of behavioral alterations mimicking some negative symptoms and partial amelioration of some cognitive defects in STOP-null mice. Interestingly, clozapine treatment also improves synaptic plasticity of the STOP- null animals by restoring long-term potentiation in the hippocampus. All together, the pharmacological reactivity of STOP-null mice to antipsychotics evokes the pharmacological response of humans to such drugs. Totally, our study suggests that STOP-null mice may provide a useful preclinical model to evaluate pharmacological properties of antipsychotic drugs.